Preliminary Results on Prompt \(\Xi^+/\Xi^-\) Production ratio in \(pp\) Collisions at \(\sqrt{s} = 7~\text{TeV}\) - Chung, Nguyen Mau; Dung, Nguyen Thi; Tam, Tran Minh (Communications in Physics, 2011)
The ratio of prompt \(\Xi^+/\Xi^-\) production has been investigated from a limitedsample of data registered by the LHCb experiment at the CERN Large Hadron Colliderin 2010. This ratio has been determined in the rapidity region \(1.9 \leq y \leq 4.9\) covered bythe LHCb detector. The determination of anti-hyperons to hyperons production ratio willallow to study the transport of baryon number from pp collisions to final state hadrons andto constrain and tune Monte Carlo models